Open Banking and Working Capital Efficiency: Evidence from API Adoption - Budianto, Hendy (Jurnal Informatika Ekonomi Bisnis, 2025)
This study aims to examine the effect of Open Banking adoption through Application Programming Interfaces (APIs) on corporate working capital efficiency in Indonesia. Employing a quantitative explanatory approach, the research involved 90 respondents consisting of finance managers, accounting staff, and fintech decision-makers across multiple industrial sectors. Data were collected via an online survey using a five-point Likert scale and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The findings reveal that API-based Open Banking adoption has a significant positive effect on working capital efficiency (β=0.482; p<0.001). This effect is mediated by data transparency and processing speed, enabling firms to accelerate cash conversion cycles, shorten receivable periods, and enhance liquidity management accuracy. Furthermore, the level of financial digitalization strengthens the relationship between API adoption and working capital efficiency, while firm size shows no significant impact. These results support the Resource-Based View and Dynamic Capabilities theories within the digital finance context and enrich the literature on Open Banking’s role in fostering financial efficiency and operational excellence. Practically, the study provides insights for policymakers and financial institutions to promote broader API integration within corporate financial systems.